Chemical Effects of CO2 Concentration on Soot Formation in Jet-stirred/Plug-flow Reactor - 张引弟 娄春 刘德华 李勇 阮龙飞 (Chinese journal of chemical engineering, 2013)
Soot formation was investigated numerically with CO2 addition in a jet-stirred/plug-flow reactor （JSR/PFR） C2H4/OJN2 reactor （C/O ratio of 2.2） at atmospheric pressure. An updated Kazakov mechanism empha- sizes the effect of the O2/CO2 atmosphere instead of an O2/N2 one in the premixed flame. The soot formation was taken into account in the JSR/PFR for C2H4/O2/N2. The effects of CO2 addition on soot formation in different C2H4/O2/CO2/N2 atmospheres were studied, with special emphasis on the chemical effect. The simulation shows that the endothermic reaction CO2 ＋ H - CO ＋ OH is responsible of the reduction of hydrocarbon intermediates in the CO2 added combustion through the supplementary formation of hydroxyl radicals. The competition of CO2 for H radical through the above forward reaction with the single most important chain branching reaction H ＋ O2, ＇ O ＋ OH reduces significantly the fuel burning rate. The chemical effects of CO2 cause a significant increase in residence time and mole fractions of CO and OH, significant decreases in some intermediates （H, C2H2）, polycyclic aromatic hydrocarbons （PAHs, C6H6 and CI6H10, etc.） and soot volume fraction. The CO2 addition will leads to a decrease by only about 5% to 20% of the maximum mole fractions of some C3 to Clo hydrocarbon intermediates. The sensitivity analysis and reaction-path analysis results show that C2H4 reaction path and products are altered due to the CO2 addition.